Socio-economic and ethnocultural influences on geographical disparities in breast cancer screening participation in Victoria, Australia - Stuart, Geoffrey W.; Chamberlain, James A.; Milne, Roger L. (Frontiers in Oncology, 2022)
Objective To examine the socio-economic and ethnocultural characteristics of geographical areas that may influence variation in breast cancer screening participation. Methods In a cross-sectional analysis breast cancer screening participation for statistical areas in Victoria, Australia (2015-2017) was linked with data from the 2016 Australian Census. We selected four commonly used area-level measures of socio-economic status from the Australian Census (i) income (ii) educational level (iii) occupational status and (iv) employment profile. To assess the ethnocultural characteristics of statistical areas we used the Census measures (i) country of birth (ii) language spoken at home (iii) fluency in English (iv) religion and (v) the proportion of immigrants in an area, together with their recency of migration. Results All the selected measures were related to screening participation. There was a high degree of association both within and between socio-economic and ethnocultural characteristics of areas as they relate to screening. Ethnocultural characteristics alone accounted for most of the explained geographical disparity in screening participation. Conclusions Geographical disparities in breast cancer screening participation may be due to ethnocultural factors that are confounded with socio-economic factors.